2021
DOI: 10.14238/sp22.5.2021.277-84
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Karakteristik Ibu, Pengetahuan, dan Praktik Pemberian Makanan Pendamping Air Susu Ibu pada Bayi di Kota Pontianak

Abstract: Latar belakang. Stunting adalah masalah malnutrisi balita di Indonesia. Di Kalimantan Barat, prevalensinya 33,3% berdasarkan data Riskesdas 2018. Praktik pemberian MPASI yang tidak optimal berkontribusi besar pada angka itu.Tujuan. Sebagai langkah awal dalam pencegahan stunting dilakukan survei untuk mengetahui gambaran karakteristik ibu, pengetahuan, dan praktik pemberian MPASI pada bayi di kota Pontianak.Metode. Studi potong lintang dilakukan pada bulan November- Desember 2018 di tiga Puskesmas Kecamatan Kot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Discrepancies in maternal knowledge lead to inappropriate complementary feeding practices in Indonesia, not only in mothers with low socioeconomic status, but also in mothers with higher socioeconomic status. 7 The main theme of complementary feeding practices was broken down into four sub-themes: "on time" (Tepat waktu), "adequate" (Adekuat), "safe" (Aman), and "responsive feeding" (Makan responsif), further abbreviated as TAAMa for mothers to remember. The module was was developed in accordance with the WHO Global Strategy for Feeding Infant and Young Children (2003) requirements for proper complementary feeding.…”
Section: Sub-theme Expert Nmentioning
confidence: 99%
See 2 more Smart Citations
“…Discrepancies in maternal knowledge lead to inappropriate complementary feeding practices in Indonesia, not only in mothers with low socioeconomic status, but also in mothers with higher socioeconomic status. 7 The main theme of complementary feeding practices was broken down into four sub-themes: "on time" (Tepat waktu), "adequate" (Adekuat), "safe" (Aman), and "responsive feeding" (Makan responsif), further abbreviated as TAAMa for mothers to remember. The module was was developed in accordance with the WHO Global Strategy for Feeding Infant and Young Children (2003) requirements for proper complementary feeding.…”
Section: Sub-theme Expert Nmentioning
confidence: 99%
“…A study in Pontianak, Indonesia showed that 87.3% of mothers think oil should not be given in children younger than 9 months of age. 7 Some Indonesian mothers engage in unhelpful activities while feeding their babies, such as watching television or digital devices (65.5%), scolding their babies while feeding (14.5%), or forcing their children to eat (11.8%). 7 These results exposed several complementary feeding problems in Indonesia and revealed the need for comprehensive multidisciplinary management to deal with malnutrition in Indonesia.…”
mentioning
confidence: 99%
See 1 more Smart Citation